The Phr1 ubiquitin ligase promotes injury-induced axon self-destruction - Babetto, Elisabetta (2013)
Axon degeneration is an evolutionarily conserved process that drives the loss of damaged axons and is an early event in many neurological disorders, and so it is important to identify the molecular constituents of this poorly understood mechanism. Here we demonstrate that the Phr1 E3 ubiquitin ligase is a central component of this axon degeneration program. Loss of Phr1 results in prolonged survival of severed axons both in the peripheral and central nervous systems, as well as preservation of motor and sensory nerve terminals. Phr1 depletion increases the axonal level of the axon survival molecule nicotinamide mononucleotide adenyltransferase 2 (NMNAT2), and NMNAT2 is necessary to mediate Phr1-dependent axon stability. The profound long-term protection of peripheral and central mammalian axons following Phr1 deletion suggests that pharmacological inhibition of Phr1 function may be an attractive therapeutic candidate for ameliorating axon loss in neurological disease.